Ének Debóráról: A Magyarországi Református Egyház lelkésznőinek helyzete (Szociológiai Szemle, 2024)
In the present paper I have examined a very complex situation related to gender discrimination within the Reformed Church of Hungary. Recently one cannot see any discrimination at the level o f legal regulation, but at the same time there are a lot of contradictions in practice, concerning the real position of women-members of the Reformed Church of Hungary. The jurisdiction of the church has cancelled any gender discrimination but this is not reflected in the mind of the members o f the congregation, priests, priestesses, etc. The priestesses have the most immediate experience in all these at the Church. What can be the reason of it? In certain attitutes only „the males” are responsible for all the problems. According to my hypothesis , „the females” contribute to the evil condition as well. During the theoretical and empirical investigations it has turned out that they are unsatisfied with their absurd position but they do not have any strategy for solving the problems. The majority of them shrink back from assuming real (public) responsibility and think that it is far better when „the males” occupy the leading role and decisionmaking positions. The basis of all these is a socialized lack of self-confiedence, which is strenthened by a certain trend in the Church.